Mapping the flow of veterinary antibiotics in Kenya - Morang’a, Alexina K.; Muloi, Dishon M.; Kamau, Simon M.; Onono, J.O.; Gathura, P.B.; Moodley, Arshnee (Frontiers Media, 2024)
Introduction: To effectively regulate and reduce antibiotic use, in the livestock sector, a thorough understanding of the flow of veterinary antibiotics will help to identify key nodes in the chain for targeted interventions. The aim of this study was to understand the flow of antibiotics from import to end-user, and identify relevant governance mechanisms.